2018
DOI: 10.4236/arsci.2018.61003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian Hormone and Follicle Counts as Predictors of Superovulatory Response and Embryo Production in Beef Cattle

Abstract: This study evaluated Anti-Mullerian hormone (AMH) and/or follicle counts as predictors of subsequent superovulatory response and embryo production in 79 beef cows. Before superovulation, 3 to 5 mm follicles presented on the ovaries of donor cows were counted, and blood was collected for measure of serum AMH. Across cows, serum AMH ranged from 0.013 to 0.898 ng/mL, with a mean of 0.293 ng/mL. The distribution of both AMH concentrations and follicle counts were divided into quartiles (AMH Q1 through Q4, with Q1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
5
15
0
1
Order By: Relevance
“…Based on AMH concentrations of the donor's cows before super-stimulation, the means of CL, total ovarian response, transferable and freezable embryos were significant (P<0.01) higher for cows group having AMH ≥230ng/L. In agreement with our findings, low category of AMH was adopted <200ng/L with poor ovarian response and the high category >400ng/L with good response and more produce embryos in cattle [15,18] and buffaloes [60]. Similarly, Monniaux [17] determine cows with >200ng/L of AMH were produced more embryos than cows having ≤200ng/L of AMH.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Based on AMH concentrations of the donor's cows before super-stimulation, the means of CL, total ovarian response, transferable and freezable embryos were significant (P<0.01) higher for cows group having AMH ≥230ng/L. In agreement with our findings, low category of AMH was adopted <200ng/L with poor ovarian response and the high category >400ng/L with good response and more produce embryos in cattle [15,18] and buffaloes [60]. Similarly, Monniaux [17] determine cows with >200ng/L of AMH were produced more embryos than cows having ≤200ng/L of AMH.…”
Section: Discussionsupporting
confidence: 88%
“…The study herein showed that, the correlations between AMH concentrations and ovarian response were significant positive (P<0.05) for CL (r=0.36), total ovarian response (P<0.01; r=0.80), transferable embryos (r=0.32), and freezable embryos (r=0.35). Similar correlations were reported by other researchers [15,17,18,[54][55][56]. AMH produced by granulosa cells of the ovarian follicles [57] and the numbers of ovarian follicles are variable across females and highly repeatable within individuals [16,24].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…İnek ve düvelerde ortalama AMH düzeyi sırasıyla 0.26±0.17 ve 0.21±0.16 ng/ml±SD olarak belirlendi. İneklerde bir bireyin AMH düzeyi siklus boyunca nispeten stabil olmasına rağmen bireyler arasındaki farkın oldukça yüksek olduğu belirtilmektedir (9,11). İnek ve düvelerin minumum ve maksimum AMH değerleri arasında farklılıklar olduğu görülmektedir.…”
Section: Discussionunclassified